2020
DOI: 10.7441/soced.2020.08.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Environmental literacy of pupils and its investigation in the Czech Republic

Abstract: Environmental literacy is a concept consisting of knowledge, attitudes, sensitivity and behaviour. In this text we present a pilot study of a research tool focused on measuring the environmental literacy of ISCED 2 pupils. Through the study we measured the relationship between environmental literacy and selected variables (gender, grade and leisure activities). The target group consisted of pupils in the 6th to 9th grades of lower secondary schools, and the total number of respondents was 467. The inner consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…A significant relationship between the affective and conative dimensions was identified, for example, by Whitburn et al (2020), while a connection with the cognitive dimension was not demonstrated. Analogous conclusions are provided by many other studies (Svobodová, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…A significant relationship between the affective and conative dimensions was identified, for example, by Whitburn et al (2020), while a connection with the cognitive dimension was not demonstrated. Analogous conclusions are provided by many other studies (Svobodová, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Issue identification, issue analysis and action planning). The tool was successfully validated mainly in the American environment (McBeth et al, 2008(McBeth et al, , 2011McBeth & Volk, 2009;Stevenson et al, 2013Stevenson et al, , 2014, also in Greece (Nastoulas et al, 2017) and the Czech Republic (Svobodova 2020;Svobodova & Chval, 2022).…”
Section: Environmental Literacymentioning
confidence: 99%